(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Extensive research has been carried out concerning the planning of flexible manufacturing systems (FMS), primarily focusing on established academic layout strategies. This research predominantly draws from fundamental principles within the intelligent system JSSE (workshop scheduling environment), with limited existing literature addressing its specific application within an FMS context. The primary objective of this article is to assess the effectiveness of scheduling models for machines and AGVs (Automated Guided Vehicles) in reducing the number of operations within the FMS, using an approach based on the Hadoop Scheduler (HS). The research methodology is subject to evaluation across a range of experimental conditions, utilizing an FMS simulation model that encompasses 40 distinct scenarios.